Refining Macroeconomic Policies to Sustain Growth in Brazil - Mourougane, Annabelle (OECD Economics Department Working Papers, 2011)
This paper identifies refinements to the macroeconomic framework that will help Brazil to achieve strong performance in a new environment in which population will age at a rapid pace, heavy reliance on oil resources will increase public revenue volatility and uncertainties regarding the external environment are higher, possibly permanently. More specifically, the country needs to pursue fiscal consolidation and remove existing rigidities in the budget process. Over the medium term, moving to a headline budget target would ensure long-term sustainability of public (including social security) accounts, and introducing an expenditure ceiling and removing widespread revenue earmarking would help restrain expenditure. Adopting the proposals to simplify the tax system currently under discussion would improve the business environment, and the government should persevere in its effort to secure political support for them from the states. A pressing challenge is to adapt current transfer mechanisms to ensure regional and inter-generational equity in sharing oil revenues. The establishment of the social fund, which is designed to save part of the oil windfalls and whose investment returns will be allocated to social spending, could help these equity objectives to be reached, so long as it is well designed. The ongoing surge in capital inflows complicates the task of monetary policy and should be addressed through a range of policies, in which fiscal consolidation features prominently. Additional measures such as macro-prudential policies or a temporary tax on short-term capital inflows could also help to prevent the formation of asset price bubbles. This Working Paper relates to the 2011 OECD Economic Review of Brazil 2011 (www.oecd.org/eco/surveys/Brazil)